Unveiling high specific energy supercapacitor from layer-by-layer assembled polypyrrole/graphene oxide with polypyrrole/manganese oxide electrode material - Kulandaivalu, Shalini; Suhaimi, Nadhrah; Sulaiman, Yusran (Nature Publishing Group, 2019)
A novel layer-by-layer (LBL) based electrode material for supercapacitor consists of polypyrrole/graphene oxide and polypyrrole/manganese oxide (PPy/GO|PPy/MnO2) has prepared by electrochemical deposition. The formation of LBL assembled nanocomposite is confirmed by Fourier transform infrared spectroscopy, Raman spectroscopy and X-ray diffraction. The field emission scanning electron microscopy images clearly showed that PPy/MnO2 was uniformly coated on PPy/GO. The PPy/GO|PPy/MnO2 symmetrical supercapacitor has revealed outstanding supercapacitive performance with a high specific capacitance of 786.6 F/g, an exceptionally high specific energy of 52.3 Wh/kg at a specific power of 1392.9 W/kg and preserve a good cycling stability over 1000 cycles. It is certain that PPy/GO|PPy/MnO2 has an extraordinary perspective as an electrode for future supercapacitor developments. This finding contributes to a significant impact on the evolution of electrochemical supercapacitor.